Long-term challenge of methylphenidate changes the neuronal population and membrane property of dopaminergic neuron in rats. (January 2019) - Hsu, Sanford PC.; Wang, Dao-Yuan; Min, Ming-Yuan; Fu, Yu-Show
Abstract: Attention deficit hyperactivity disorder (ADHD) has a prevalence of 7.5% in school-age children in Taiwan. A number of ADHD patients start taking medications in elementary school and continue their treatment until they are in college or adulthood. Methylphenidate is the most frequently used medication prescribed for ADHD treatment. The influence of long-term treatment of methylphenidate on neuro-development, especially dopaminergic neurons, in rats would be explored. This study investigated the impact of long-term treatment of methylphenidate on different neurons. Rats aged 1 month were divided into three groups: Normal group receiving only sucrose solution, Low-dose group receiving 2 mg/kg methylphenidate, and High-dose group receiving 10 mg/kg methylphenidate; for each group, the drug was administrated twice per day. After 7 months of the treatment period, then the alterations in number of norepinephrine, serotonergic, cholinergic and dopaminergic neurons were quantified. The number of dopaminergic neurons in the substantia nigra (SN), the serotonergic neurons in the dorsal raphe nucleus, and the cholinergic neurons in the tegmental nucleus significantly decreased as compared with Normal group, whereas the noradrenergic neurons in the locus coeruleus substantially increased. The whole-cell recording was made from dopaminergic neurons residing in the SN for examination of their firing activity. The recorded dopaminergic neurons in SN were categorized into slow and fast firing using 10 Hz as a classified index. The results displayed that the ratio of dopaminergic neurons with fast firing in the High-dose group was less as compared with those in the Normal and the Low-dose group. Furthermore, the amplitude of action potential of the dopaminergic neurons with slow firing was higher in the High-dose group than those in the Normal and Low-dose groups. The firing behavior of dopaminergic neurons and dopamine concentration in the brain is affected by the long-term challenge of methylphenidate. Highlights: Attention deficit hyperactivity disorder (ADHD) is the most prevalent neurobehavioral disorders in children. To increase learning effectiveness, most ADHD children take medicine from the age of the elementary school to college. Methylphenidate (brand name: Ritalin) is the most common clinically used medication. The number and electrophysiological property of dopaminergic neurons display changes after long term treatment of Ritalin.